The influence of customer satisfaction and shariah view on customers loyalty of Islamic banking - Jamaludin, Nur Fatin Hazwani; Zakaria, Nur Hasniza; Mohd Aminuddin, Nur Liyana (2015)
The aim of this study was to analyse "The influence of customer satisfaction and shariah view on customers loyalty of Islamic banking". The study was conducted and focus on customers of Islamic banking in Kota Bharu, Kelantan. 94 of questionnaire were distributed to 94 respondents. The research methodology is quantitative that used to have the better result. In order to analyse data, Statistic Package (SPSS) was used in this study. The result showed that "The influence of customer satisfaction and shariah view on customers loyalty of Islamic banking" are acceptable.